Introduction: Compiling ‘Endangered Knowledge’ - MacFarlane, Samantha; Mattson, Rachel; Nowviskie, Bethany (KULA, 2018)
This essay introduces a special issue of KULA on the subject of ‘endangered knowledge,’ comprising 22 essays by 34 authors working across a wide array of disciplines and fields. Guest editors Samantha MacFarlane, Rachel Mattson, and Bethany Nowviskie have assembled a collection of scholarly articles, pedagogical reflections, and project reports that take up theoretical and practical considerations of archival salvage and erasure, the persistence of the public record, indigenous knowledge, and the politics of loss. The special issue explores endangerment as a critical category of analysis for records, data, collections, languages, ecosystems, and networks.